Voltage‐sensitive sodium channel mutations S989P + V1016G in Aedes aegypti confer variable resistance to pyrethroids, DDT and oxadiazines - Smith, Letícia B; Kasai, Shinji; Scott, Jeffrey G (Pest management science, 2018)
BACKGROUND Aedes aegypti is a vector of several important human pathogens. Control efforts rely primarily on pyrethroid insecticides for adult mosquito control, especially during disease outbreaks. A. aegypti has developed resistance nearly everywhere it occurs and insecticides are used. An important mechanism of resistance is due to mutations in the voltage‐sensitive sodium channel (Vssc) gene. Two mutations, in particular, S989P + V1016G, commonly occur together in parts of Asia. RESULTS We have created a strain (KDR:ROCK) that contains the Vssc mutations S989P + V1016G as the only mechanism of pyrethroid resistance within the genetic background of Rockefeller (ROCK), a susceptible lab strain. We created KDR:ROCK by crossing the pyrethroid‐resistant strain Singapore with ROCK followed by four backcrosses with ROCK and Vssc S989P + V1016G genotype selections. We determined the levels of resistance conferred to 17 structurally diverse pyrethroids, the organochloride DDT, and oxadiazines (VSSC blockers) indoxacarb (proinsecticide) and DCJW (the active metabolite of indoxacarb). Levels of resistance to the pyrethroids were variable, ranging from 21‐ to 107‐fold, but no clear pattern between resistance and chemical structure was observed. Resistance is inherited as an incompletely recessive trait. KDR:ROCK had a > 2000‐fold resistance to DDT, 37.5‐fold cross‐resistance to indoxacarb and 13.4‐fold cross‐resistance to DCJW. CONCLUSION Etofenprox (and DDT) should be avoided in areas where Vssc mutations S989P + V1016G exist at high frequencies. We found that pyrethroid structure cannot be used to predict the level of resistance conferred by kdr. These results provide useful information for resistance management and for better understanding pyrethroid interactions with VSSC. © 2017 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry. This article demonstrates the contribution of two Vssc mutations, S989P+V1016G, to insecticide resistance in A. aegypti, an important human disease vector. We discuss pyrethroid structure and cross‐resistance to oxadiazines.